2022
DOI: 10.3390/nu14091879
|View full text |Cite
|
Sign up to set email alerts
|

Oral Supplement Containing Hydroxytyrosol and Punicalagin Improves Dyslipidemia in an Adult Population without Co-Adjuvant Treatment: A Randomized, Double-Blind, Controlled and Crossover Trial

Abstract: Hydroxytyrosol (HT) and punicalagin (PC) exert cardioprotective and antiatherosclerotic effects. This study evaluated the effect of an oral supplement containing HT and PC (SAx) on dyslipidemia in an adult population. A randomized, double-blind, controlled, crossover trial was conducted over a 20-week period. SAx significantly reduced the plasma levels of triglycerides (TG) in subjects with hypertriglyceridemia (≥150 mg/dL) (from 200.67 ± 51.38 to 155.33 ± 42.44 mg/dL; p < 0.05), while no such effects were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 102 publications
0
6
0
Order By: Relevance
“…Malondialdehyde (MDA) was determined spectrophotometrically with a commercial kit (Oxford Biomedical Research, Rochester Hills, Mich, colorimetric assay for lipid peroxidation; measurement range 1–20 nmol/L) 15 . For MDA, the intra‐assay variability was 3.39%, respectively, and the inter‐assay 6 variability was 4.75%, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Malondialdehyde (MDA) was determined spectrophotometrically with a commercial kit (Oxford Biomedical Research, Rochester Hills, Mich, colorimetric assay for lipid peroxidation; measurement range 1–20 nmol/L) 15 . For MDA, the intra‐assay variability was 3.39%, respectively, and the inter‐assay 6 variability was 4.75%, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, HT reduced the serum interleukin‐6 (IL‐6) and C‐reactive protein (CRP) levels in mice 13 and had comparable action with aspirin in inhibiting of collagen‐induced platelet aggregation in whole blood 14 . Previous studies have shown a beneficial effect of olive oil extract supplements on endothelial function in subjects without known cardiovascular disease 15 . However, the effects of olive oil supplements on cardiovascular function in patients with chronic coronary artery syndrome (CCAS) have not been fully defined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… [ 39 ] Eligible human patients (n = 30) Control group Extract group For 8 weeks 1 group consumed placebo and the other an extract from OO and AS EG decreased oxLDL levels and it improved oxLDL/LDL-col ratio. [ 40 ] Eligible human patients (n = 84) SAx supplement Placebo 3 capsules/day of the assigned product during 20 weeks separated into 8 weeks of treatment (supplement or placebo) by a washout period of 4 weeks. Supplementation decreased LDL and TG levels while it increases HDL levels.…”
Section: The Effect Of Hydroxytyrosol In Human Studiesmentioning
confidence: 99%
“…The interventional product contained 3.3 mg of HT, 65 mg of PC and 331.7 mg of maltodextrin. Upon the intervention period, lipid profile improved notoriously by the decrease of LDL (p < 0.004), increase of HDL (p < 0.033) and decrease of TG (p < 0.017) [ 40 ] ( ClinicalTrials.gov , NCT02042742). Thus, the evidences presented in these clinical trials suggest that HT has a great pharmacological potential.…”
Section: The Effect Of Hydroxytyrosol In Human Studiesmentioning
confidence: 99%